Implementasi Fungsi Manajemen Pada Pembelajaran Kitab Akhlaqul Banin Untuk Meningkatkan Akhlakul Karimah di Pondok Pesantren Hidayatul Mubtadi’in Jati Agung Lampung Selatan - Agung Supriono; Agus Sujarwo; Taqwatul Uliyah (EDU SOCIETY: JURNAL PENDIDIKAN, ILMU SOSIAL DAN PENGABDIAN KEPADA MASYARAKAT, 2025)
The purpose of this study is to analyze the implementation of management functions in the integrated learning of the Akhlaqul Banin Book at the Hidayatul Mubtadi’in Jati Agung Islamic Boarding School with a focus on improving students’ morals. This study uses a descriptive qualitative approach to understand the implementation of management functions in the learning of the Akhlaqul Banin Book at the Hidayatul Mubtadi’in Jati Agung Islamic Boarding School and its influence on students’ morals. Data were collected through in-depth interviews, participant observation, and documentation studies, analyzed thematically based on management functions and moral indicators such as discipline, politeness, responsibility, and empathy. Data triangulation was used to ensure validity, while informants were selected by purposive sampling. The results of the study indicate that the success of the Akhlaqul Banin Book learning in improving morals at the Hidayatul Mubtadi’in Jati Agung Islamic Boarding School is influenced by the implementation of structured and consistent management functions, including planning, organizing, and directing. Careful planning establishes moral targets such as discipline, courtesy, responsibility, and empathy, while organizing the tasks of teachers, caregivers, and group mentors ensures guidance tailored to the students' needs. Active guidance through lectures, practices, and daily moral guidance fosters students' motivation to emulate and internalize moral practices. The integration of these three management functions creates a holistic learning mechanism that supports character formation, behavioral transformation, and the ongoing internalization of noble morals within the Islamic boarding school environment.